SCENARIO OF INDIAN RETAIL INDUSTRY (International Journal of Food and Nutritional Sciences, 2023)
Retailing in India is undergoing a transformation and is one of the most important sectors in the global economy. India is a potential goldmine for both international and domestic retail players. India now ranks as the 5th most attractive international destination for the retailing business. It is expected that Indian retail business could be worth US$ 1,470 billion by 2026. India's retail journey began from ancient times. As stated by various experts, India has a long history of going from local retailing to international retailing business. Globally, Indian retail industry achieved the 1st ranking in Global Retail Development Index. But due to the impact of COVID-19, this industry drop down to 2nd position after China. But, for Food & Grocery retail segment, pandemic become beneficial. With multiple firms entering the market, India's retail business has emerged as one of the most dynamic and competitive industry. The retail industry in India is steadily gaining traction as the next big industry. This paper focus on the growing trend of retail industry of India during the COVID-19 in the country.